Open-cathode hydrogen experimental of 5-watt polymer exchange membrane fuel cell / Mahanijah Md Kamal - Md Kamal, Mahanijah; Tarmizi, Mohamad Zaimi; Mohamad Zulkhairie Chee, Mohd Ridwan (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
In this work, an analysis of an open-cathode hydrogen pressure based on experimental approach was conducted at Alternative Energy Research Centre, Faculty of Mechanical Engineering Universiti Teknologi MARA Shah Alam. The polymer electrolyte membrane (PEM) fuel cell is a custombuilt device consisting of five membranes or cells. The aim is to observe the polarization curve of 5 watt PEM fuel cell. The experiment on the PEM fuel cell has been conducted for data collection and analysis. The performance of fuel cells was measured by varying the hydrogen supply (supplied at the anode side and the relative humidity. The outputs of PEM fuel cell were measured in net power, watt and stak voltage, volt where the curve was plotted. The result obtained from the experiment shows a similarity in the trend of the polarization characteristic curve.